Anticipatory Planning in Children with Autism Spectrum Disorder: An Assessment of Independent and Joint Action Tasks - Scharoun, Sara M.; Bryden, Pamela J. (Frontiers in Integrative Neuroscience, 2016)
Autism Spectrum Disorder (ASD) is one of the most common neurodevelopmental disorders. Although not a diagnostic feature, motor impairments have been recently acknowledged as prevalent and significant, such that these children have difficulties planning, organizing and coordinating movements. This study aimed to further investigate anticipatory motor planning in children with ASD by means of assessing end- and beginning-state comfort, considering inconsistent reports of end-state comfort in independent action, and the study of beginning-state comfort being limited to one study with young adults. Five- to 11-year-old children with ASD, and chronologically age- and sex matched typically-developing children picked-up a glass and (1) poured a cup of water; and (2) passed it to the researcher to pour a cup of water. End-state comfort was deemed evident if participants grasped the glass thumb-down followed by a 180° rotation; therefore ending with a thumb-up posture. Beginning-state comfort was deemed evident if participants passed the glass to the researcher oriented upright. Findings revealed less end-state comfort in children with ASD, attributed to motor planning deficits. Beginning-state comfort did not differ, ascribed to the habitual nature of the task; therefore reflecting a stimulus-driven response as opposed to an action which reflects anticipatory planning. Findings support difficulties with motor planning and control for children with ASD in an independent task. However, when acting with a familiar object in joint action, behaviour does not differ, likely indicative of a habitual, stimulus-driven response.